2021
DOI: 10.3389/fpsyg.2020.627980
|View full text |Cite
|
Sign up to set email alerts
|

Combined Vision and Hearing Difficulties Results in Higher Levels of Depression and Chronic Anxiety: Data From a Large Sample of Spanish Adults

Abstract: ObjectiveIndividually, vision and hearing impairments have been linked to higher levels of anxiety and depression. We investigated the effect of dual sensory impairment (difficulty seeing and hearing) in a large representative sample of Spanish adults.MethodsData from a total of 23,089 adults (age range: 15–103 years, 45.9% men) from the Spanish National Health Survey 2017 were analyzed. Self-reported difficulty of seeing and hearing (exposures), and depression and chronic anxiety (outcomes) were analyzed. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In other words, sensory impairment in older adults can not only aggravate physical discomfort 55 and contribute to an increase in disability, but also limit daily activity performance 56 and reduce the quality of lifestyle behaviors, which might induce anxiety. 57 This progressive and persistent negative impact makes most older people feel helpless and sensitive due to the fear of physical health, being a burden to the families or even not being accepted by society, 58 thus increasing the risk of depressive symptoms 58 and strongly being associated with poor cognitive function. 59 There are some limitations of this study that need to be noted:…”
Section: T a B L Ementioning
confidence: 99%
“…In other words, sensory impairment in older adults can not only aggravate physical discomfort 55 and contribute to an increase in disability, but also limit daily activity performance 56 and reduce the quality of lifestyle behaviors, which might induce anxiety. 57 This progressive and persistent negative impact makes most older people feel helpless and sensitive due to the fear of physical health, being a burden to the families or even not being accepted by society, 58 thus increasing the risk of depressive symptoms 58 and strongly being associated with poor cognitive function. 59 There are some limitations of this study that need to be noted:…”
Section: T a B L Ementioning
confidence: 99%
“…Some cross-sectional studies have found a positive association between dual sensory difficulty and depression (Heine et al, 2019). Several cross-sectional studies that compared the association across sensory difficulties reported the strongest association among those with dual sensory impairment (Hajek and König, 2020;Rong et al, 2020;Pardhan et al, 2021b). In contrast, one study showed a cross-sectional relationship between depression and both visual and dual sensory difficulty but not between hearing difficulty and depression (Chou and Chi, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of DSI extend well beyond cognitive impairment. Pardhan et al 6 researched the impact of DSI on depression and chronic anxiety among 23,089 adults participating in the Spanish National Health Survey of 2017. The researchers analyzed self-reported vision, hearing, depression, and chronic anxiety and found that vision or hearing impairment was significantly associated with higher odds for depression (OR = 2.37, 95% CI = 2.04 – 2.75 and 2.1, 95% CI = 1.67 – 2.64, respectively) and highest for DSI (OR = 3.86, 95% CI = 2.72 – 5.44).…”
Section: What Are the Consequences Of Dsi?mentioning
confidence: 99%